Developing the core national strength and conditioning association - Willardson, Jeffrey M. (Sport performance series, 2014)
"Elite-level athletes take great pride in their fitness and physical strength. You can?t help but notice the muscular legs or well-defined arms. However, whether they are known for a powerful golf swing or a hard hockey slap shot, the best athletes all have one thing in common?a strong and well-conditioned core. The world?s leading organization in the field of sport conditioning, the National Strength and Conditioning Association (NSCA), brings you the authoritative resource on strengthening the core to maximize sport performance. With contributions by 17 of the top names in sport training, conditioning, and science, Developing the Core features over 50 of the most effective exercises, science-based assessment tools, sport-specific programs, and expert advice for developing a personalized core program. Basketball, football, soccer, golf, baseball, tennis?no matter what your sort, Developing the Core will place you on the path to success and your strongest midsection ever." -- from publisher's website